Risk of Dental Caries and Erosive Tooth Wear in 117 Children and Adolescents' Anorexia Nervosa Population—A Case-Control Study - Paszynska, Elzbieta; Hernik, Amadeusz; Slopien, Agnieszka; Roszak, Magdalena; Jowik, Katarzyna; Dmitrzak-Weglarz, Monika; Tyszkiewicz-Nwafor, Marta (Frontiers in Psychiatry, 2022)
Introduction Restrictive type of anorexia nervosa (AN) is still one of the most severe eating disorders worldwide with an uncertain prognosis. Patients affected by AN should be encouraged to undertake psychiatric care and psychotherapy, but whether they should necessarily be included in careful dental care or not may still be questionable. Even though there is a constantly increasing number of AN studies, there are just a few data about the youngest group of AN children and adolescents aged < 18. Methodology This case-control study aimed to compare the dental health and gingival inflammation level in female adolescent inpatients affected by severe AN restrictive subtype vs. controls. Based on clinically confirmed 117 AN cases (hospitalized in years 2016–2020 in public Psychiatric Unit, BMI < 15 kg/m2, mean age 14.9 ± 1.8), the dental status has been examined regarding the occurrence of caries lesions using Decay Missing Filling Teeth (DMFT), erosive wear as Basic Erosive Wear Examination (BEWE), gingival condition as Bleeding on Probing (BOP) and plaque deposition as Plaque Control Record (PCR). The results were compared with age-matched 103 female dental patients (BMI 19.8 ± 2.3 kg/m2, age 15.0 ± 1.8, p = 0.746) treated in a public University dental clinic. Results AN patients were found to present a higher incidence of oral-related complications according to dental status (DMFT 3.8 ± 4.5 vs. 1.9 ± 2.1, p = 0.005), erosive tooth wear (BEWE 18.9 vs. 2.9%, p < 0.001), less efficient in controlling plaque (PCR 43.8 vs. 13.7%, p < 0.001) and gingival inflammation (BOP 20.0 vs. 3.9%, p < 0.001) compared with female adolescents. In the AN group, a significant correlation between BOP, BEWE, and duration of AN disease (p < 0.05), similarly to the number of decayed teeth D, filled teeth F and PCR were detected (p < 0.05). Conclusions Although the obtained results did not reveal any severe oral status, our findings indicated impaired dental and gingival conditions in young anorexics. Considering AN's potential role in oral health, it is essential to monitor dental treatment needs and oral hygiene levels in their present status to prevent forward complications in the future.